An investigation of the reproducibility and usefulness of automatic couch motion in complex radiation therapy techniques - Woo, Milton K. (J Appl Clin Med Phys, 2002)
Radiation therapy techniques that incorporate multiple couch motions are becoming more common, and they often involve an increasing level of complexity along with a need for automatic motion. The reproducibility of automatic couch motion is thus a growing concern. In this work we carried out various tests to assess the automatic motion of a commercial treatment couch, including tests to evaluate the digital readout reproducibility, as well as an independent verification of the reproducibility of the couch positions on repeated motions, using phantoms as well as a volunteer subject. It was shown that the couch motion is highly reproducible, with no discomfort to the patient, and can greatly improve treatment times as well as reduce errors in couch positioning. PACS number(s): 87.52.–g, 87.53.–j